Thermogravimetric Kinetic Analysis of Non-Recyclable Waste CO2 Gasification with Catalysts Using Coats–Redfern Method - Ahmad Mohamed S. H. Al-Moftah; Richard Marsh; Julian Steer (ChemEngineering, 2022)
In the present study, the effect of dolomite and olivine as catalysts on the carbon dioxide (CO2) gasification of a candidate renewable solid recovered fuel, known as Subcoal™ was determined. Thermogravimetric analysis (TGA) was used to produce the TGA curves and derivative thermogravimetry (DTG) for the gasification reaction at different loadings of the catalyst (5, 10, 15 wt.%). The XRD results showed that the crystallinity proportion in Subcoal™ powder and ash was 42% and 38%, respectively. The Arrhenius constants of the gasification reaction were estimated using the model-fitting Coats–Redfern (CR) method. The results showed that the mass loss reaction time and thermal degradation decreased with the increase in catalyst content. The degradation reaction for complete conversion mainly consists of three sequences: dehydration, devolatilisation, and char/ash formation. The complete amount of thermal degradation of the Subcoal™ sample obtained with dolomite was lower than with olivine. In terms of kinetic analysis, 19 mechanism models of heterogeneous solid-state reaction were compared by the CR method to identify the most applicable model to the case in consideration. Among all models, G14 provided excellent linearity for dolomite and G15 for olivine at 15 wt.% of catalyst. Both catalysts reduced the activation energy (<semantics>Ea</semantics>) as the concentration increased. However, dolomite displayed higher CO2 gasification efficiency of catalysis and reduction in <semantics>Ea</semantics>. At 15 wt.% loading, the <semantics>Ea</semantics> was 41.1 and 77.5 kJ/mol for dolomite and olivine, respectively. Calcination of the mineral catalyst is substantial in improving the activity through enlarging the active surface area and number of pores. In light of the study findings, dolomite is a suitable mineral catalyst for the industrial-scale of non-recyclable waste such as Subcoal™ gasification.